The Transition from the Inquisitorial to the Accusatorial System of Trial - Leonard L. Cavise (My University, 2016)
The article is born of my experience teaching American-style trial advocacy to over 15 groups of Latin American lawyers coming from countries in transition from the inquisitorial to the accusatorial model. The first part of the article reviews the principal differences in the two systems as it affects trial procedure. The article then reviews those aspects of accusatorial trial proceedings that caused the greatest degree of discomfort to the foreign lawyers. Finally, the article attempts to posit a few recommendations that should help not only to ease the transition process but also to anticipate the next level of procedural and substantive obstacles.